РОЛЬ МУЛЬТИМЕДИЙНЫХ СРЕДСТВ В ОБУЧЕНИИ АНГЛИЙСКОМУ ЯЗЫКУ СТУДЕНТОВ НЕЯЗЫКОВЫХ ФАКУЛЬТЕТОВ - Каипбергенова, Ф.Т. (SCIENCE and SOCIETY, 2025)
The article discusses the importance and effectiveness of multimedia in teaching English to students of non-linguistic faculties. In addition, the study examines the challenges and opportunities of incorporating these tools into the curriculum and highlights their potential to help create engaging and exciting learning experiences for learners of varying backgrounds.
Keywords: multimedia tools; language learning; English education; interactive learning; motivation; comprehension; virtual reality; language acquisition; digital platforms